Análise experimental da ligação entre placas de painéis sanduíches unidas com treliça metálica - Knöner, Nery (Universidade Federal de São Carlos, 2019)
ABSTRACT A.KNONER, N Study on the stiffness between membranes and design of sandwich panels in reinforced concrete 2019. thesis (PhD) in structures and Civil Engineering-Federal University of São Carlos, São Carlos UFSCAr, 2019. The prefabricated concrete construction meets the need for more economic constructions and with greater speed of execution and, in search of construction processes more efficient and contribute to the improvement of quality in the process, the production of elements and in the execution of the work, were the basis of this research aimed to study and analyze the design of sandwich type panels bearing walls in precast concrete, as an option of a constructive system for multiple floors buildings. This study was characterized as an exploratory research, because it took into account the absence of similar searches to developed and had participation in preparation of models in the factory environment, taking the technology to the domestic market. So, the search had the theoretical-experimental for the distribution of the horizontal and vertical efforts between concrete membranes and their connectors to better understand the functioning and your project. The methodology covered the theoretical study of the behaviour and design of concrete membranes, allowing yourself to know the percentage of stiffness between them, knowing how the degree of action the dashboard; In addition, tests were carried out in the laboratory of sandwich panels, with different arrangements of filling and connections both to bending about sharp edges between membranes. According to the results, the bending behavior presented good proximity to the experimental and theoretical values, showing the possibility of doing a project and the tests of shear strength (stiffness) resistance to slip between the panels tested it was observed that due to the number of broken diagonals, it has not been possible to obtain the exact relationship of the applied load and sliding. As a conclusion, we can say that it is possible to apply the calculation model for the design of panels with a good approximation of the results and that more studies must be done in order to implement this technology in the country and incorporate the brazilian standard.
Experimental analysis of the connection between united sandwich panel plates with metallic gate
Keywords: Painel Sanduíche; Concreto pré-moldado; Rigidez entre placas de um painel; Comportamento estrutural; Sandwich panel; Precast concrete; Strength between a panel plates; Structural behavior; ENGENHARIAS::ENGENHARIA CIVIL